PENGOLAHAN DATA HONOR MENGAJAR DOSEN PADA STMIK PRADNYA PARAMITA MALANG DENGAN PENDEKATAN DATA WAREHOUSE - Mumpuni, Indah Dwi (DINAMIKA DOTCOM, 2013)
Teaching faculty salary data processing by using a data warehouse is to support the presentation of information in the decision-making process of leadership, academic and financial sections. The method used is the method of analysis and design method. The results achieved are in the form of Data Warehouse design and prototype simulation data warehouse that contains data and can be further analyzed for decision making. The end result of the design of the data warehouse is used to simplify and speed up the data access and gives full access to the corporate leaders of historical data without performing data processing operations. With the data warehouse can be generated structured data collection and well integrated as an input to the management in the decision making process.Â Keywords: Data Warehouse, salaries of teaching faculty